2018
DOI: 10.1177/1179544118781094
|View full text |Cite
|
Sign up to set email alerts
|

Retrocalcaneal Bursitis Precedes or Accompanies Achilles Tendon Enthesitis in the Early Phase of Rheumatoid Arthritis

Abstract: The consecutive reports and stored images of ultrasound examinations for 100 symptomatic ankles of 74 patients with rheumatoid arthritis (RA) were reviewed for the presence or absence of retrocalcaneal bursitis (RCB) and Achilles tendon enthesitis (ATE). The ankles were classified into 4 categories based on the presence or absence of RCB or ATE. The number of RCB(−)/ATE(−), RCB(+)/ATE(−), RCB(+)/ATE(+), and RCB(−)/ATE(+) ankles was 62, 16, 12, and 10, respectively. When classifying patients into early RA and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…10) [13]. Suzuki et al [14] recently reported that retrocalcaneal bursitis could be preceded or accompanied by Achilles tendon enthesitis and suggested that synovio-entheseal complex inflammation in RA arises from synovial tissues, supporting the concept proposed by McGonagle et al [12].…”
Section: B Cmentioning
confidence: 78%
“…10) [13]. Suzuki et al [14] recently reported that retrocalcaneal bursitis could be preceded or accompanied by Achilles tendon enthesitis and suggested that synovio-entheseal complex inflammation in RA arises from synovial tissues, supporting the concept proposed by McGonagle et al [12].…”
Section: B Cmentioning
confidence: 78%
“…Conversely, some patients have tendon thickening without a typical focal intratendinous signal. Early retrocalcaneal bursitis may be seen because inflammation ascends from the synovial membrane lining the walls of the bursa [ 48 ].…”
Section: Arthritismentioning
confidence: 99%